ANALISIS PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN DALAM PENILAIAN KINERJA PUSAT PENDAPATAN PT.SUMBER SATWA SEJAHTERA DI MEDAN - Dayani Pohan, Tasya Rahma; Syafina, Laylan (Universitas Prof.Hazairin,SH Bengkulu, 2022)
The study identified the problems as follows: Revenue realization has not reached the budgeted target, and Budget difference has not fully benefited because there is a significant decrease in actuality in 2019 to 2021. have not got the set budget and know how to apply responsibility accounting in evaluating the performance of revenue centers. This research method uses a literature review with a descriptive approach, part of qualitative research methods. Has the aim of collecting scientific data and information in the form of theories, books, and journals as solutions and the basis for arguments. The qualitative method refers to an in-depth understanding of specific main ideas. It is concluded that the existing revenue performance assessment still has complex problems and requires a lot of improvement, starting from internal and external constraints. The approach taken must also use Top-Down because it can clarify the authority and responsibility in each section and division and be guided directly from the leadership to the staff and employees of PT. Sumber Satwa Sejahtera. The approach used is Top-Down to clarify each division's authority and responsibility. The fact is that actual income does not match the estimated revenue due to changes in circumstances such as changes in the price of chickens per unit/kilogram, several sick chickens, loss of dead chickens, The increase in the price of essential commodities, the increase in selling prices due to deteriorating economic changes and the Covid-19 pandemic that hit Indonesia resulted in several restaurants being temporarily closed (lockdown).